Geology and geotechnics of the Coca hydroelectric project, Napo province. - Décker Coello, Ernesto (Revista Universidad de Guayaquil, 1990)
The Eastern foothills of the Andes Mountains have been barely studied. This is due to the little initiative demonstrated by government and private institutions in establishing an inventory of resources in those areas. INECEL, within a work program, has placed great interest in the use of Hydroelectric Resources in the Quijos-Coca River Basin. With this Bachelor Thesis, the Author, who participated in the various stages of the studies, aims to discover the Regional Geology of the Project, local Geology of the site proposed for the El Salado exploitation and a study of the construction materials .